The Tecnological values Required for Kindergarten Teacher and their Role in the Professionalizing Of Education (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
The current study aimed to determine the level of kindergarten teachers’ commitment to technological values in their professional practice from their perspective, and to examine the role of technological values in enhancing the professionalism of kindergarten teachers and developing their performance, also considering the significance of differences in the teachers’ average questionnaire scores according to variables such as educational qualification, training courses, and years of experience. The study adopted a descriptive-analytical approach, and the sample consisted of 130 kindergarten teachers. A questionnaire comprising 30 items was used, distributed across two domains: the first domain addressed the teachers’ commitment to technological values in professional practice, while the second examined the role of technological values in enhancing the teachers’ professionalism and improving their performance.The results indicated that the level of kindergarten teachers’ commitment to technological values in professional practice, from their perspective, was high. Likewise, the role of technological values in enhancing teachers’ professionalism and developing their performance was high. There were no statistically significant differences in the teachers’ average scores on the questionnaire according to educational qualification or years of experience, whereas differences were statistically significant according to training courses, in favor of those who had attended such courses.
Keywords: Technological values, kindergarten teachers, professionalization of Education